2015
DOI: 10.3892/or.2015.3746
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic effect of endocannabinoids in prostate cancer cells

Abstract: In the early stages, prostate cancer is androgen- dependent; therefore, medical castration has shown significant results during the initial stages of this pathology. Despite this early effect, advanced prostate cancer is resilient to such treatment. Recent evidence shows that derivatives of Cannabis sativa and its analogs may exert a protective effect against different types of oncologic pathologies. The purpose of the present study was to detect the presence of cannabinoid receptors (CB1 and CB2) on cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 43 publications
(51 reference statements)
1
63
0
2
Order By: Relevance
“…Several studies have demonstrated the anti-proliferative and proapoptotic effect of a variety of cannabinoids in prostate cancer, including the endocannabinoids anandamide and 2-arachidonoyl glycerol, and phytocannabinoids cannabidiol and tetrahydrocannabinol. 5,[17][18][19] We have shown that treatment with the synthetic cannabinoid WIN significantly inhibits cell proliferation and induces apoptosis in human prostate cancer cells in a dose-dependent manner (Figures 1, 3A, and 3B, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated the anti-proliferative and proapoptotic effect of a variety of cannabinoids in prostate cancer, including the endocannabinoids anandamide and 2-arachidonoyl glycerol, and phytocannabinoids cannabidiol and tetrahydrocannabinol. 5,[17][18][19] We have shown that treatment with the synthetic cannabinoid WIN significantly inhibits cell proliferation and induces apoptosis in human prostate cancer cells in a dose-dependent manner (Figures 1, 3A, and 3B, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…In prostate carcinomas, expressions of both CB 1 and CB 2 receptors were increased compared to the normal prostatic tissue (Orellana‐Serradell et al, ), and the overexpression of CB 1 receptors has been associated with a higher Gleason score and metastasis incidence, being a negative marker of disease outcome. (Chung et al, ; Cipriano et al, ).…”
Section: Endocannabinoid System Expression In Cancermentioning
confidence: 99%
“…Similarly, activation of either CB 1 or CB 2 receptors with THC was demonstrated to induce an inhibitory effect on ERK and Akt in human Jurkat leukaemia T cells (Jia et al, ). However, in prostate cancer cells, the apoptosis induced by eCBs (either AEA or 2‐AG) acting on CB 1 receptors was found to be the result of an inhibitory effect on the Akt pathway whereas the ERK signalling cascade was activated (Orellana‐Serradell et al, ).…”
Section: Effect Of the Endocannabinoid Signalling Pathways On Cell Dementioning
confidence: 99%